Emerging microbes & infections (NPG, 2012)
"The purpose of EMI is to provide a forum to publish a wide range of scientific reports related to emerging infectious diseases, especially with new information from developing countries where such diseases are constantly arising and being discovered regularly. It will report discoveries of emerging microbes (bacteria, viruses, fungi and other pathogens) including their previously unknown phenotypic or genotypic characteristics, as well as cutting edge information associated with microbial mechanisms of pathogenesis, immune evasion and protection, clinical presentation and outcome, drug efficacy and its resistance, epidemiology and other issues important to global health."
Keywords: Emerging infectious diseases : Periodicals; Emerging infectious diseases : Pathogenesis : Periodicals; Emerging infectious diseases : Epidemiology : Periodicals; Emerging infectious diseases; Emerging infectious diseases : Epidemiology; Communicable Diseases, Emerging; Communicable Diseases